Analysis of Culture Shock in Cross-Cultural Communication of Local and Immortal Students in The Faculty of Social Sciences, State Islamic University of North Sumatra - Riza, Muhammad Raihan; Yusniah (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
communication between local and immigrant students at the Faculty of Social Sciences, State Islamic University of North Sumatra. Using the theory of intercultural communication and the concept of culture shock from Oberg, this study applies a qualitative ethnographic approach with a constructivist paradigm. Data were collected through in-depth interviews, participant observation, and documentation, and validated using source triangulation. The results of the study indicate that local students have difficulty understanding the accent and regional terms of immigrant students, while immigrant students face discomfort in communicating and feelings of inferiority in initial interactions. Through involvement in campus organizations and academic activities, immigrant students successfully adapt, while local students show an attitude of openness to cultural diversity. The conclusion of the study confirms that cross-cultural interactions on campus show developments towards more inclusive social relations, although institutional efforts are still needed to systematically strengthen cross-cultural programs in order to optimize the social integration of students from various backgrounds.